Zika virus and birth defects: an obstetric issue - Okeke, Tochukwu C.; Ezenyeaku, Cyril C.; Ikeako, Lawrence C.; Okeke, Kenechukwu O.; Onyekwulu, Fidelis A.; Okafor, Christain I.; Adiri, Charles O. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Zika virus is an emerging mosquito-borne virus that is relatively unknown, unstudied and under-diagnosed, but has potentials to spread to new geographical areas that favour survival of Aedes mosquitoes. It is associated with an alarming rise in babies with microcephaly that require much care and support with a lot of financial assistance. This is a review article on Zika virus and birth defects; a worrisome issue in today’s obstetric and medical practices. Since Zika’s discovery in Uganda, the virus was known to occur within a narrow equatorial belt from Africa to Asia with no or mild symptoms. It has emerged as a global public health threat over the last decade with accelerated geographic spread of the virus in the last nine years. The risk of Zika virus to the fetus is poorly understood, difficult to quantify and problematic. The causal link between Zika virus and microcephaly was initially speculative, strongly suspected and scientifically unproven. However, on 13th April, 2016, it was concluded that Zika virus is the cause of microcephaly and other severe fetal brain defects. The Center for Disease Control and Prevention (CDC) authors reviewed and weighed evidences using established scientific criteria to conclude after a careful review of the report published in the New England Journal of Medicine. There is no prophylaxis, treatment or vaccine to protect against Zika virus infection. However, preventive personal measures are highly recommended to avoid mosquito bites.